AN ANALYSIS MODALITY IN MALEFICENT 1 MOVIE SCRIPT - Agnes Caroline Baene; Miranda Wangisari Padang; Arsen Nahum Pasaribu (Institut Pendidikan Tapanuli Selatan, 2022)
This research paper focuses on examining the modality in a movie script entitled Maleficent 1. The researcher sees that there are many sentence structures that are very interesting because they have the meaning of modality. Modality is divided into 2 types, namely modalization and modulation. The data taken are movie scripts sourced from the internet and watch movies from YouTube. The research method uses Descriptive Qualitative research methods which explain the meaning in a clause that contains part of the modality type Thus, the research data consist that around 83 data were found in all categories. The most dominant type of modality is obligation 43(51.8%), and then is respectively followed by Probability 19 (22. 8%), usuality 15(18%), and inclination 6(7.2%). The findings indicate the language of the movie used the high modulation obligation as the most dominant type of modality.